(untitled) (The Review of Diabetic Studies, 2025)
The development of evidence-based nursing interventions is critical to improving patient safety and quality improvement in the Saudi healthcare, which follows the transformation program of the Health Sector, Health Sector Transformation Program (HSTP), of Vision 2030. The systematic review summarizes the literature published between 2020-2025 on such interventions as standardized protocols, interprofessional education (IPE), error reporting systems, and technology integration. Based on 28 studies, it was found that there were positive safety outcomes such as 25-35% decreases in medication errors and ventilator-associated pneumonia under the introduction of EBP, yet the barriers of time (56-94%), resource (shortage) issues, and cultural resistance remain. The EBP knowledge of nurses is moderate (scores 3.7-6.74/22) with leadership support and training facilitators providing the highest 20-33% literacy increase. The main interventions are summarized in tables, graphs are used to visualize trends of prevalence and outcomes of barriers. The debate criticizes city bias and implementation, and suggestions promote compulsory IPE, computerized technology, and policy changes. The review highlights the importance of nursing in ensuring equitable and high care in the Saudi environments to minimize adverse events and enhance sustainability.